Comprehensive genome-wide identification and functional analysis of the GT8 gene family in Eucalyptus Grandis - Jie, Yufan; Liu, Liwan; Li, Linsi; Wu, Ai-Min; Fan, Chunjie; Liu, Siwen (Frontiers in Plant Science, 2025)
IntroductionThe Glycosyltransferase 8 (GT8) family is critically involved in plant cell wall synthesis, yet exhibits significant functional divergence among its members. Despite its importance, systematic characterization of GT8 genes in woody plants remains limited. This study aims to comprehensively analyze the GT8 gene family in Eucalyptus grandis to elucidate its role in cell wall biosynthesis.MethodsWe employed bioinformatics tools to mine the E. grandis whole-genome database. A systematic analysis was conducted, including phylogenetic classification, assessment of physicochemical properties, subcellular localization prediction, gene structure annotation, chromosome mapping, and cis-acting element identification in promoter regions.ResultsFifty-two GT8 family members were identified and classified into four subfamilies: GAUT, GATL, GolS, and PGSIP. Protein molecular weights ranged from 15.75 to 185.00 kD (mean: 49.08 kD). Genes were dispersed across all chromosomes except chromosomes 3 and 7. Promoter analysis revealed ubiquitous hormone-responsive cis-elements and prevalent light-responsive elements. Phylogenetic inference suggested that EgGUX02 and EgGUX04 may mediate glucuronic acid (GlcA) incorporation into xylan side chains, while EgGAUT1 and EgGAUT12 are likely direct contributors to xylan and pectin biosynthesis.DiscussionThis study provides the first genome-wide functional annotation of the GT8 family in E. grandis, revealing subfamily-specific roles in cell wall polymer synthesis. The enrichment of stress- and hormone-responsive promoter elements implies regulatory complexity in cell wall remodeling. Our findings establish a foundation for targeted manipulation of xylan and pectin biosynthesis in woody plants, with potential applications in biomass engineering.